Impact of nutrition education in improving dietary pattern during pregnancy based on pender's health promotion model: A randomized clinical trial - Masoomeh Goodarzi-Khoigani; Mohammad Hossein Baghiani Moghadam; Azadeh Nadjarzadeh; Farahnaz Mardanian; Hossein Fallahzadeh; SeyedSaeed Mazloomy-Mahmoodabad (Wolters Kluwer Medknow Publications, 2018)
Background: Different types of nutrients in adequate amounts are required to meet the increased demands of the mother and the developing fetus. Therefore, we examined the impact of nutrition education on the number of food servings per day. Materials and Methods: Pregnant mothers were recruited to a prospective, randomized clinical trial from May to September, 2016. At 6-10 weeks of gestation, the participants were randomly divided into the intervention (n = 96) or the control group (n = 96), and were followed-up until the end of pregnancy. Each woman in the experimental group met the study nutritionist at the time of enrollment and an individualized nutrition plan was developed. In addition, the nutrition education based on Pender's Health Promotion Model (HPM) was designed, including three 45-60 min training sessions in 6-10, 18, and 26 weeks of pregnancy. The participants' usual food intake using a three-day dietary record was assessed at 6-10 weeks and 34-36 weeks of gestation. Results: The mean scores of the perceived benefits, self-efficacy, activity-related affect, interpersonal influences (husband support), and commitment to action increased while the competing demand scores decreased in the interventional group compared with the control group. The mean standard deviation (SD) of food portions from grain [10.40 (1.96) versus 12.70 (1.93) in the control group], vegetable [3.88 (1.33) versus 2.96 (0.91)], fruit [4.02 (0.05) versus 3.95 (0.91)], dairy [2.33 (0.68) versus 2.11 (0.45)], and meat [3.17 (0.68) versus 2.96 (0.67)] were improved in the experimental group. Conclusions: Pender's HPM for nutrition education is effective based on the compliance of pregnant women to the dietary guideline and the food guide pyramid.